Eslicarbazepine and the enhancement of slow inactivation of voltage-gated sodium channels: A comparison with carbamazepine, oxcarbazepine and lacosamide. (February 2015) - Hebeisen, Simon; Pires, Nuno; Loureiro, Ana I.; Bonifácio, Maria João; Palma, Nuno; Whyment, Andrew; Spanswick, David; Soares-da-Silva, Patrício
Abstract: This study aimed at evaluating the effects of eslicarbazepine, carbamazepine (CBZ), oxcarbazepine (OXC) and lacosamide (LCM) on the fast and slow inactivated states of voltage-gated sodium channels (VGSC). The anti-epileptiform activity was evaluated in mouse isolated hippocampal slices. The anticonvulsant effects were evaluated in MES and the 6-Hz psychomotor tests. The whole-cell patch-clamp technique was used to investigate the effects of eslicarbazepine, CBZ, OXC and LCM on sodium channels endogenously expressed in N1E-115 mouse neuroblastoma cells. CBZ and eslicarbazepine exhibit similar concentration dependent suppression of epileptiform activity in hippocampal slices. In N1E-115 mouse neuroblastoma cells, at a concentration of 250 μM, the voltage dependence of the fast inactivation was not influenced by eslicarbazepine, whereas LCM, CBZ and OXC shifted the V 0.5 value (mV) by −4.8,  −12.0 and −16.6, respectively. Eslicarbazepine- and LCM-treated fast-inactivated channels recovered similarly to control conditions, whereas CBZ- and OXC-treated channels required longer pulses to recover. CBZ, eslicarbazepine and LCM shifted the voltage dependence of the slow inactivation ( V 0.5, mV) by −4.6,  −31.2 and −53.3, respectively. For eslicarbazepine, LCM, CBZ and OXC, the affinity to the slow inactivated state was 5.9, 10.4, 1.7 and 1.8 times higher than to the channels in the resting state, respectively. In conclusion, eslicarbazepine did not share with CBZ and OXC the ability to alter fast inactivation of VGSC. Both eslicarbazepine and LCM reduce VGSC availability through enhancement of slow inactivation, but LCM demonstrated higher interaction with VGSC in the resting state and with fast inactivation gating. Highlights: Eslicarbazepine did not share with carbamazepine and oxcarbazepine the ability to alter fast inactivation of VGSC. Eslicarbazepine and lacosamide reduce VGSC availability through enhancement of slow inactivation. Lacosamide demonstrated higher interaction with VGSC in the resting state and with fast inactivation gating.